Association of CD4 cell counts and viral load with cystatin C level in children with human immunodeficiency virus (HIV) infection - Wita Rostania; Anggraini Alam; Dany Hilmanto (Indonesian Pediatric Society, 2023)
Background The ease of access to antiretroviral therapy (ART) has improved both survival rate and comorbidities in patients with human immunodeficiency virus (HIV) infection. Impaired kidney function is one of the most common comorbidities of HIV. CD4 and viral load can be used to monitor HIV progression and to determine the effectiveness of ART. The most commonly used estimated-glomerular filtration rate (e-GFR) technique is to use serum creatinine but often causes late detection of kidney dysfunction while serum cystatin increases at the beginning of the GFR decrease. This supports cystatin C serum as an early diagnostic tool to detect kidney function or biomarker early kidney disorders. Objective To evaluate a possible association between serum cystatin C as a marker of kidney function and HIV progression through CD4 levels and viral load. Methods This cross-sectional study was conducted through evaluation of secondary data from medical and laboratory records of pediatric patients who had routine visits to the HIV Clinic at Dr. Hasan Sadikin General Hospital, Bandung, West Java, in January-February 2020. Results Sixty subjects were reviewed in the study. Median cystatin C-based eGFR was 28.1mL/minute/1.73m2. Subjects were categorized by viral load result into <40 and ?40 copies/mL. The median serum cystatin C was significantly higher [3.7 (range 2.61–6.55) mg/L] in the >40 copies/mL viral load group than the <40 copies/mL group [2.4 (range 0.26–13.61) mg/L]. The median absolute CD4 count, CD4 percentage, and cystatin C were 776 (range 7–1644) cells/mm3, 27.5 (range 1.6–57.4) %, and 3 (range 0.26–13.61) mg/L, respectively. There were no significant correlations (r=-0.2; P=0.1) between CD4 and serum cystatin C Conclusion Higher viral load associates with higher cystatin C level, while CD4 shows no correlation to cystatin C. However, patients with low CD4 tend to have increased cystatin C level.